Effect of Calf Delivery Mode on Irisin, Asprosin, Leptin, Adiponectin, and Insulin-Like Growth Factor-1 Levels in Dairy Cattle and their Calves - Kizil, Meltem; Risvanli, Ali; Abay, Murat; Safak, Tarik; Kilinc, Mehmet Akif; Yilmaz, Oznur; Seker, Ibrahim (Zoological Soc Pakistan, 2023)
In recent years, the investigation of peptide and protein-structured hormones in biological fluids has become one of the most striking issues. The aim of this study was to determine irisin, asprosin, leptin, adiponectin, and IGF-1 levels in cows and calves after calving according to the mode of delivery. The study was carried out with 20 Holstein cows and 20 calves born from these cows. Blood samples were taken from cows and calves in all groups during birth, after drinking colostrum from calves and on the 15th, 30th, 45th and 60th days after birth in 10 ml tubes. The levels of the aforementioned molecules in these blood samples were determined by ELISA method. Feeding with colostrum led to a decrease in the irisin levels in the dystocia and cesarean section groups and in the IGF-1 levels in the vaginal delivery group, but it did not lead to any other significant changes. The irisin levels of the calves in the vaginal delivery group were compared to those in the other groups, and their levels were found to decrease on the 15th day, and IGF-1 levels were higher on the 15th day. As a result, it was revealed that there were significant changes in the levels of these molecules in the umbilical cord and blood serum of cows and calves depending on the mode of delivery.
Keywords: Adiponectin; Asprosin; Calf; Irisin; Leptin